2017
DOI: 10.24327/ijcar.2017.2388.0014
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological spectrum of papanicolaou smears - a hospital based retrospective study

Abstract: Cervical cancer is second most common cancer of women in India. Screening of cervical cytology by simple papinocolou smear is an effective tool to detect premalignant lesions of cervix. Present study was retrospectively done to determine the cytomorphological spectrum of various cervical lesions and categorize them according to Bethesda system .All the patients presenting in gynaecological OPD and health camps with gynaecological complaints were included and subjected for PAP smear. Most common complaint and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
3
1
0
Order By: Relevance
“…O et al 20 whereas K K Innaniya et al 15 reported 41-60 years as the most common age group. In our study Negative for intraepithelial lesion or malignancy (NILM) was seen in 93.24% which was similar in a study done by Sachan PL et al, 16 Sharma A et al, 18 K.K Innaniya et al, 15 Bhattacharya N B et al, 8 Verma A. et al 19 However, Kumar N et al 10 and Shaki O et al 20 In the present study ASCUS, ASC-H, LSIL, HSIL, and AGUC NOS were 2.06 %, 0.14%, 0.52%, 0.23%, and 0.33% respectively. No squamous cell carcinoma case was found.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…O et al 20 whereas K K Innaniya et al 15 reported 41-60 years as the most common age group. In our study Negative for intraepithelial lesion or malignancy (NILM) was seen in 93.24% which was similar in a study done by Sachan PL et al, 16 Sharma A et al, 18 K.K Innaniya et al, 15 Bhattacharya N B et al, 8 Verma A. et al 19 However, Kumar N et al 10 and Shaki O et al 20 In the present study ASCUS, ASC-H, LSIL, HSIL, and AGUC NOS were 2.06 %, 0.14%, 0.52%, 0.23%, and 0.33% respectively. No squamous cell carcinoma case was found.…”
Section: Discussionsupporting
confidence: 90%
“…The most common chief complaint was vaginal discharge which was like in other studies. 13,14,16,[18][19][20] The most common age group of presentation in our study was 31-40 years which was like the study done by Ninder kumar et al, 10 Rana et al, 17 Verma A et al, 19 Shaki. O et al 20 whereas K K Innaniya et al 15 reported 41-60 years as the most common age group.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations